The Burrowing Barnacles (Cirripedia, Acrothoracica) of South Africa - Botha, Thomas Petrus Arnoldus (Department of Biological Sciences, 2020)
The Acrothoracica of South Africa are reviewed for the first time, 50 years after the last publication on this group appeared. A new host category for acrothoracicans is described in Chapter 1, as Weltneria spinosa was collected from coralline red algae. This finding was not an isolated event, as this species was found inhabiting four different species of coralline algae across a range of sites up to 900 km apart. These are the first unequivocal records of living acrothoracicans burrowing into coralline red algae. Further inspections of coralline algae in this and other regions will likely reveal many more new host records and possibly new acrothoracican species. In Chapter 2 a systematic account and key to all known South African acrothoracicans are given, with each description accompanied by scanning electron microscopy, light microscopy and a distribution map. The number of known South African acrothoracicans is increased from four to eight species, as three new records and two undescribed species are added to the fauna, while one existing record is determined to be a nomen nudum. Chapter 3 examines patterns of distribution and host specificity. All species except one saw a range extension, some of which were > 500 km, while all species had additional hosts described. The species with the most hosts was W. spinosa, which was reported from 13 hosts that included gastropods, chitons and coralline red algae. South Africa thus now includes 11.27% of the world’s acrothoracican species, with 62.50% of these endemic. Moreover, 75% of South African acrothoracicans were endemic to specific provinces. However, these values are likely to change substantially as more sites are sampled both within the region and in neighbouring countries. In conclusion this dissertation shows that South Africa has more acrothoracican species, occupying more hosts across wider distributional ranges than previously thought. Although this study serves as a valuable baseline it should be expanded on through future sampling, specifically focusing on areas (Delagoa, Namaqua and offshore bioregions) and hosts (especially corals) not yet sampled in South Africa.